Why stop at response?. Issue 2 (July 2017) - Head, Lesley
The broad question around which I frame my dialogue with Briassoulis's paper is, why stop at response? I consider this question with three connected subquestions. Why is it only the response part of the subject matter that needs assemblage thinking? Can other conceptualizations – environmental degradation, socioecological systems – remain intact within an assemblage approach? And does the concept of response itself imply a linear kind of causality arguably incompatible with assemblages?